Sarna psoróptica em um rebanho ovino no município de São Vicente do Sul, Rio Grande do Sul, Brasil - Jardim Filho, José Osvaldo (2020)
Mite Psoroptes ovis is the agent of sheep psoroptic mange, one of the most severe sheep skin disease. It’s a highly itchy and contagious disease responsible for major economic losses in sheep producing countries. It’s characterized by the formation of large lesions covered by a yellowish and scaly crust, accompanied by damage to wool and leather. P. ovis belongs to the order Astigmata, family Psoroptidae and genus Psoroptes. The entire cycle is completed on the surface of the host's skin in 10 to 14 days and transmission occurs mainly by contact. The study that composes this Dissertation describes an outbreak of sheep psoroptic mange in a property in the municipality of São Vicente do Sul, in the Midwest Rio Grande do Sul region, Brazil. Poor nutritional status, restless behavior, pruritus, wool fall, yellowish crusted skin lesions with edge exudate, erythema surrounding the lesions and presence of wool trapped between the teeth were observed in the herd. Complete blood count test showed marked eosinophilia, and parasitological examination of a skin scrape revealed P. ovis. Histopathological examination of a skin biopsy sample revealed eosinophilic pustular dermatitis. The treatment consisted of two administrations of 1% ivermectin at 1 mL/33 kg of body weight subcutaneously over an interval of 10 days. There are no other published scientific studies reporting the occurrence of this disease, its clinical signs, or laboratory or histopathological findings in this region; although, its occurrence has been recorded in the state by the Official Veterinary Service. This lack of information is probably contributing to the difficulty in diagnosing sheep scab in RS by veterinarians working at rural properties in the state. researchers should investigate the occurrence of this parasitic infection in RS and performed characterization of its clinical manifestation to better guide professionals, thus contributing to its control.